THE “PROTOCOL” STUDY: PRELIMINARY RESULTS - E. M. Zelenskaya; A. I. Subbotovskaya; V. I. Ganyukov; N. A. Kochergin; V. B. Barbarich; N. O. Saraeva; A. V. Vybivantseva; K. A. Apartsin; G. I. Lifshitz (Российский кардиологический журнал, 2015)
Aim. To reveal the association of gene polymorphism CYP2С19*2 and recurrent early stent thrombosis in coronary vessels, and paradoxal response to clopidogrel intake in patients — the inhabitants of Siberian Region — after acute coronary syndrome.Material and methods. Totally 105 patients studied, hospitalized for stenting of coronary arteries in acute coronary syndrome, never received clopidogrel previously. The polymorphism of studied СУР2С19: *2, *3, *17 alleles, as assessment of platelet aggregation with ADP before and after clopidogrel intake, as of endpoints on safety and efficacy during 30 days (thrombotic complications, bleeding).Results. Within the selected patients there was no any significant association of any CYP2С19*2 and/or CYP2С19*3 alleles and paradoxic laboratory reaction. There was significant association of the CYP2C19*17 gene carriage and bleedings. When comparing the groups of patients having or not having complications related to clopidogrel (thrombotic or bleedings), there was significant difference in residual platelet aggregation.Conclusion. The results of the study might be strongly significant for the decisions making on double antiplatelet therapy and on the tactics of drugs preference.